Sensemaking of Stakeholder Identity Construction in Determining Potential Social Assistance Recipients - Sidharta, Veranus; Lubis, Djuara P.; Sarwoprasodjo, Sarwititi; Seminar, Kudang Boro (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
Implementation of the social assistance policy program to determine social assistance recipients in the context of development communication involves stakeholder action in the sensemaking process as an effort to achieve a common understanding in determining who is worthy of receiving social assistance. Previous research stated that the problems that still occur today are weak communication and coordination between institutions, distribution of social assistance that does not match targets, unclear distribution mechanisms and data on social assistance recipients that are not in sync, lack of integration of one Indonesian data, misidentification, and neglect of groups. vulnerable, deceased social assistance recipients are still registered, identity of social assistance recipients is not registered in DTKS or SIKS-NG, problematic social assistance recipients are still registered, NIK is invalid, inactive social assistance recipients still receive assistance, multiple social assistance recipients. The aim of this research is to understand the sensemaking process used by stakeholders in determining potential social assistance recipients. The approach used in this research is descriptive qualitative using a constructivist paradigm and case study design. The research results show the important role of identity construction of local leaders, especially village heads, in data management and distribution of social assistance. Through a reflective and participatory approach, local leaders can ensure the accuracy and honesty of data on social assistance recipients, as well as increase the overall effectiveness of the social assistance program. The results of this research offer a new approach in determining social assistance recipients called sensemaking.Keywords: Development communication, identity construction, sensemakingABSTRAKPelaksanaan program kebijakan bantuan sosial untuk menentukan penerima bansos dalam konteks komunikasi pembangunan melibatkan tindakan pemangku kepentingan pada proses sensemaking sebagai upaya mencapai pemahaman bersama dalam menentukan siapa yang layak penerima bansos. Penelitian sebelumnya menyatakan, permasalahan yang masih terjadi hingga saat ini adalah lemahnya komunikasi dan koordinasi antar lembaga, penyaluran bansos yang tidak sesuai target sasaran, ketidakjelasan mekanisme penyaluran dan data penerima bansos yang tidak sinkron, kurangnya integrasi satu data indonesia, kesalahan identifikasi dan pengabaian terhadap kelompok rentan, penerima bansos meninggal masih terdaftar, identitas penerima bansos tidak terdaftar dalam DTKS atau SIKS-NG, penerima bansos bermasalah tetap terdaftar, NIK tidak valid, penerima bansos tidak aktif tetap menerima bantuan, penerima bansos ganda. Adapun tujuan dari penelitian ini adalah untuk memahami proses sensemaking yang digunakan pemangku kepentingan dalam menentukan calon penerima bansos. Pendekatan yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan menggunakan paradigma konstruktivis dan desain studi kasus. Hasil penelitian menunjukkan, pentingnya peran konstruksi identitas pemimpin lokal, terutama kepala desa, dalam tata kelola data dan penyaluran bansos. Melalui pendekatan reflektif dan partisipatif, pemimpin lokal dapat memastikan keakuratan dan kejujuran data penerima bansos, serta meningkatkan efektivitas program bansos secara keseluruhan. Hasil penelitian ini menawarkan pendekatan baru dalam penentuan penerima bansos yang disebut sensemaking.Kata Kunci: Komunikasi pembangunan, konstruksi identitas, sensemaking